Qualidade de sementes de soja convencional e transgênica em função da dessecação das plantas com glyphosate - Souza, Fabiany Lilyani Gonçalves [UNESP] (2013)
The maximum quality of soybean seeds is expressed in physiological maturity, but, harvest is not recommended in this phase, due to the high water content in seeds and excess leaves and green stems on the plants. With the aim of anticipating the harvest, the practice of chemical desiccation, with the herbicide glyphosate, has been studied in soybean and requires some procedures, aiming at the preservation of the physiological quality of seeds in the field. In this way, the work aimed to evaluate the physiological quality of soybean seeds of conventional and transgenic cultivars from desiccated plants with herbicide glyphosate, in various periods of desiccation. Chemical desiccation with the herbicide glyphosate (2,0L.ha-1) was performed when the phenological stages R6.0, R7.1, R7.2 and R7.3 plants of cultivars BRS 133, Conquista, BRS 243RR and BRS 246RR were achieved. Tests for evaluation of the quality of the seeds were: water content, mass of 100 seeds, germination, first count of germination, accelerated aging, emergence of seedlings in the field, speed index of seedling emergence in the field, electrical conductivity, seedling length and mass of the dry matter of seedlings. The experimental design was randomized block, arranged in plots scheme subdivided, with four repetitions, totaling 20 treatments. The parcels consisted of four cultivars (BRS 133, Conquista, BRS 243RR and BRS 246RR) and the subplots corresponded to four periods of desiccation, which corresponded to four stages of culture (R6.0, R7.1, R7.2 and R7.3) and a witness to every cultivar (without desiccation). Treatments were arranged in factorial scheme 4 cultivars x 4 times of desiccation, more witnesses and the averages were compared by t test the probability 5. The application of glyphosate in phenological stages R6.0 and R7.1 of soybean plants, conventional cultivars BRS 133 and Conquista, negatively influences the physiological ...